MACER3D—An Upgrade of MACER2D with Enhanced Subgrid Models and Gas Physics—and Its Application to Simulating AGN Feedback in a Massive Elliptical Galaxy - Haoen Zhang; Haojie Xia; Suoqing Ji; Feng Yuan; Minhang Guo; Rui Zhang; Bocheng Zhu; Yihuan Di; Aoyun He; Tingfang Su; Yuxuan Zou (The Astrophysical Journal)
We present Multiscale AGN-regulated Cosmic Ecosystem Resolver in 3D (MACER3D), a new suite of three-dimensional hydrodynamic simulations that study active galactic nuclei (AGN) feedback on galactic scales over gigayears in duration, with major enhancements in subgrid models and gas physics over its predecessor—Massive AGN Controlled Ellipticals Resolved (MACER), which is in two dimensions (hereafter MACER2D). MACER3D resolves gas dynamics from within the Bondi radius (∼25 pc) to halo scales. Combined with black hole accretion theory, it enables an accurate calculation of AGN outputs and subsequently their large-scale feedback effects. We present results from simulating an isolated elliptical galaxy with different feedback configurations. In the fiducial model with both AGN and supernova (SN) feedback, the temporal evolution of AGN luminosity and star formation rate are strongly correlated, suggesting shared dependence on the availability of gas supply for SMBH accretion and star formation. AGN duty cycles of several percent with a single-cycle timescale of ∼10 ^2 Myr agree with observations, while models with only AGN or SN feedback fail to reproduce observed cycles. While all models maintain a quiescent galaxy state, the fiducial AGN+SN feedback model results in higher star formation than no-SN feedback, suggesting SN feedback, when acting synergistically with AGN feedback, may positively impact star formation. Combined AGN and SN feedback enhances halo-scale metal enrichment compared to single-feedback models. The simulated X-ray properties match observations and predict transient cavities produced by cold-mode AGN winds from past burst events. The differences between the results obtained by MACER2D and MACER3D are also discussed.